If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b = 4b + -9 Reorder the terms: b = -9 + 4b Solving b = -9 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. b + -4b = -9 + 4b + -4b Combine like terms: b + -4b = -3b -3b = -9 + 4b + -4b Combine like terms: 4b + -4b = 0 -3b = -9 + 0 -3b = -9 Divide each side by '-3'. b = 3 Simplifying b = 3
| Y=1/2(x-4)^2-2 | | 4sin^2(x)=2cos(x) | | (cos(x)cot(x))/(1-sinx)=3 | | cosxcotx/1-sinx=3 | | 5x+15=-3x-11 | | x=5x^2+x*5 | | N+.6=n+.1+2n | | s^2+3s+8s+24= | | (1/6)^5 | | x^2+3x+24=47 | | 0=5x^2-24x+37 | | 4y+(y-1)=29 | | 4y-y+1=13 | | 5x^2+3x+24=47 | | 20=m+1 | | (2y+3)-4=9 | | k=1.6d+300 | | 3q=18 | | 10z=9z-11 | | 41=5w-9 | | a+2(a-3)=15 | | 4+4x=-24 | | -6+2*y=0 | | j+6=9 | | 7x-15=4x-6 | | -2+2*y=0 | | 6=2p | | 2u-7=-19 | | 6+2*y=0 | | 173-w=224 | | 6(y-3)=6y+7 | | n/9=16/24 |